THE IMAGE OF THE IRAQI IN THE MENTALITY OF THE ITALIANS - Jasim Muhammed, Salim (ALBAHITH ALALAMI, 2022)
Increased interest in the subject of the image because of its great and growing link to the life of the individual and society and its impact on the overall political, economic and cultural conditions. This interest is no longer confined to the images of people or institutions, but has become beyond that to the images of countries and peoples and the impact on bilateral relations between them,However, we find that the image of the Iraqi abroad remained vague and has not been scientifically recognized and the most that we can generalize are the features of the image of Arabs and Muslims abroad; and assume that the image of the Iraqi applies to them as the Iraqi is in the end an Arab or Muslim.Based on this, the research aims to identify the image of the Iraqi in the minds of Italians by carrying out a survey using a scale questionnaire distributed to 100 respondents in three Italian cities: the capital Rome in the center, Florence in the north and Reggio Calabria in the south.The results indicated that the Iraqi image in the mentality of the Italians is very ambiguous as the respondents resorted in many paragraphs to the option of "I do not know", as for the rest of the paragraphs, the results indicated that the positive side in the image of the Iraqi outweighed the negative side.The means of communication formed the main factor in building the image of the Iraqi in the mentality of the Italians; next, school; then, friends; after that, direct dealing with the Iraqis; last, the family; and finally, cinema.The study also found that the Italians do not distinguish between Iraqis on the basis of religion or whereabouts. This confirms that the image of the research applied to all Iraqis.